The sermons to the seven churches of Revelation a commentary and guide - Weima, Jeffrey A. D. (Grand Rapids, Michigan Baker Academic, a division of Baker Publishing Group, 2021)
Ephesus -- Smyrna -- Pergamum -- Thyatira -- Sardis -- Philadelphia -- Laodicea.
"A top New Testament scholar, preacher, and tour guide to the lands of the New Testament explains the meaning of the seven sermons of Revelation 2-3 and shows how these ancient messages are relevant for the church today"--
Includes bibliographical references and index
Keywords: Bible -- Commentaries; Seven churches -- Sermons -- History and criticism